Advances in vibration therapy for the treatment of osteoporosis - Lu, Xueyan; Duan, Haoyang (Frontiers in Endocrinology, 2025)
Osteoporosis is a systemic skeletal disease characterized by reduced bone density and degeneration of bone microstructure. It is prevalent among postmenopausal women and elderly individuals. Current treatments face challenges such as drug side effects, low adherence, and comorbidities. Vibration therapy, as a non-invasive physical treatment, regulates bone metabolism through mechanical stress stimulation and is emerging as an important complementary strategy in the comprehensive management of osteoporosis. This article systematically reviews the mechanisms of action and clinical efficacy of vibration therapy. Studies indicate that vibration therapy activates osteoblast differentiation pathways (e.g., the Wnt/β-catenin signaling pathway) through low-frequency mechanical vibrations, upregulates osteogenic markers (e.g., Runx2, BMP-2, OPG), and inhibits osteoclast activity, reducing the RANKL/OPG ratio to bidirectionally regulate bone metabolic balance. Further mechanistic studies on muscle dynamics show that vibration stimulation enhances muscle contractile force, promoting bone formation through mechanical loading. Clinical trials demonstrate that vibration therapy has potential in improving lumbar and hip bone density, enhancing bone biomechanical properties, and reducing fracture risk, particularly when combined with drugs such as bisphosphonates or teriparatide, showing synergistic effects. However, variability in therapeutic outcomes (e.g., insignificant improvement in trabecular structure) may be related to differences in vibration parameters (frequency, amplitude, acceleration), device types, and individual responses. The current advantages of vibration therapy lie in its ease of use, high safety, and good adherence, but its clinical application still lacks standardized parameter guidelines. Future research should establish individualized treatment protocols and a biological equivalent dose system through large-scale randomized controlled trials to promote the standardized development of this therapy.